Reactive Oxygen Species Induced by Enterobacteriaceae in Human Uroepithelial Cells - Osama Bassim Al-Saffar (Journal of Madenat Alelem University College, 2010)
Three hundred mid-stream urine specimens were collected from 300 pateints with Urinary Tract Infections (UTI). One hundred and thirty isolates were obtained from mid-stream urines specimens included: Escherichia coli (63.84%), Klebsiella spp.(23.07%), (K. oxytoca 16.15%, K. planticola 6.92% ). Enterobacter aerogenes (6.19%) and Proteus spp. (6.92%) (P. vulgaris 4.61%, P. mirabilis 2.31%). They were identified according to the cultural and biochemical properties. Patients were divided into five groups ( A, B, C, D and E) according to the pus cells level in their urine specimens. Moreover, the type and prevalence of bacterial infection in pus cells in each studied group were detected. E. coli performed the highest percentage (61.36%) in all studied groups, particularly group A. Also the study includes the assessment of ROS inducing uropathogens which in measured by using malonadialdehyde (MDA) method. The results showed that the level of ROS was significantly (P<0.05) increased according to the level of pus cells. Thus, group E showed high level of ROS (9.08 nmol/l) in comparison with other groups in this study. On the other hand, the ability of uropathogens to induce ROS was determined. E. coli isolates particularly E. coli19 showed a putative efficiency for induction of ROS (11.62 nmol/l). In contrast, K.planticola4 exhibited the lowest level of ROS (3.14 nmol/l).